2016
DOI: 10.21608/jpp.2016.46178
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Sugar Beet as Affected by Rates of Nitrogen and Yeast Under the Number of Magenisem Application

Abstract: To investigate the effect of nitrogen and yeast rate, as well as number of magnesium application on sugar beet yield and quality, two field experiments were carried out at the Experimental Farm of Sakha Agric. Res. Station, KaferEL-Sheik Governorate, Egypt, during the two successive seasons of 2013/2014 and 2014/2015. Split-split plot design was used in both growing seasons. Three nitrogen rates (75, 85 and 95 kg N/fad) were arrange in main plots, two yeast rates (10, 15 g/l) were devoted in sub-plots, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…In this concern, Sharaf, (2012), Neseim, et al (2014), Abdou. (2015, Nemeat Alla et al (2016), Ferweez, and Abd El-Monem (2018), Thalooth, et al (2019 and Sarhan et al (2020). They showed that spraying sugar beet plants with yeast extract recorded the highest values of plant growth, yield and its components and best root quality than unsprayed plants.…”
Section: Introductionmentioning
confidence: 98%
“…In this concern, Sharaf, (2012), Neseim, et al (2014), Abdou. (2015, Nemeat Alla et al (2016), Ferweez, and Abd El-Monem (2018), Thalooth, et al (2019 and Sarhan et al (2020). They showed that spraying sugar beet plants with yeast extract recorded the highest values of plant growth, yield and its components and best root quality than unsprayed plants.…”
Section: Introductionmentioning
confidence: 98%